“Music is Language and Language is Music”: Language Attitudes and Musical Choices in Cape Breton, Nova Scotia - Sparling, Heather (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2003)
AbstractIn this article, the author considers the effects of language attitudes, a sociolinguistic concern, on musical practice. This article assumes that language and music attitudes are related as different expressions in and of a common cultural context. The author demonstrates how Scots Gaelic language attitudes in Cape Breton (where a few hundred people still speak the language) have developed, and considers the possible interplay with current attitudes towards two particular Gaelic song genres. Gaelic language learners and native/fluent speakers in Cape Breton articulated distinct and opposing attitudes towards the song genre of puirt-a-beul [mouth music], and these attitudes are examined in relation to those towards the Gaelic language and compared with their response to eight-line songs, a literary Gaelic song type. Detailed musical and lyric analyses of three Gaelic songs are provided to illustrate the connection between language and music attitudes. The current attitude towards Gaelic in Cape Breton is traced through the history of language policy in Scotland and Cape Breton. These sociolinguistic and musicological analyses are supplemented with ethnographic evidence.